Comparative Analysis of the Effectiveness of the Budget Funds Use at the Regional Level - E. A. Rechkina; A. M. Terekhov; Zh. G. Popkova (Статистика и экономика)
The purpose of the study. The purpose of the paper is to assess the effectiveness of the use of regional budget expenditures on the example of the budgets of the Nizhny Novgorod and Mur-mansk regions. Materials and methods. General scientific methods are involved: analysis, synthesis, gener-alization, classification; and specifically scientific methods: dynamics analysis, correlation and re-gression analysis, neural network modeling. The information base of the study includes indexes of the execution of the federal budget of the Russian Federation (information from the Federal Treas-ury of the Russian Federation) and regional budgets published in the relevant laws of the regions; statistical data published by Rosstat. The novelty of the research approach lies in the combination of traditional and economic-mathematical methods with the use of the Cobb-Douglas production func-tion. This fact provided an opportunity to assess the impact of budget expenditures on individual factors of production that determine the volume of public product produced. The paper presents a comparative assessment of the effectiveness of budget planning based on normative and program-target methods.Results. It was found that the use of budget funds in the Murmansk region is more effective than in the Nizhny Novgorod region. In this region, starting from 2019, the priority of the task of developing a program-targeted method of budget planning has been reduced, but the region has achieved high efficiency in the use of budget funds due to rational management of budget debt. The budget of the Murmansk Region is characterized by a significant reduction in the debt burden, which reduces the share of public debt servicing costs, and the ratio of the amount of public debt to the expenditures of the regional budget by the end of 2021 approached zero. The study showed that budget expenditures have a significant positive impact on the growth of the capital factor. At the same time, the growth of budget expenditures has a more negative impact on the development of the labor factor. It was found that when using the program-target method, a number of program ex-penditures have a positive impact on the growth of the labor force in the regions, but the degree of such influence is insignificant.Conclusion. In the course of the study, the authors concluded that the efficiency of using budget funds in the Murmansk region is higher than in the Nizhny Novgorod region. This circum-stance indicates a greater influence on the efficiency of the use of budget funds of the quality factor of public debt management in comparison with the influence of the factor of the application of the program-target method of budget planning. The results of the conducted research may be useful to government agencies responsible for planning and budgeting.